Heading and Leading Educational Institutions in Rural Africa: A Western Trained Educationists Experiences in Ghana - Otu, William (Asian Journal of Social Sciences and Management Studies, 2016)
The observation and experiential study talks about the demanding role of institutional heads and leaders in Africa; taking into consideration the culture and norms of governance in rural traditional Africa. The study also took a look at the traditional leadership in Africa, its leadership style, and its influence on its local societies and communities. Case study was used to illustrate the study.